Digital dermoscopy: a complementary method in the diagnosis of scabies, - Elaine Dias Melo; Carla Barros da Rocha Ribas; Isabel Cristina Lima Encarnação (Sociedade Brasileira de Dermatologia, 2020)
Abstract Scabies is an ectoparasitosis caused by Sarcoptes scabiei var. hominis, characterized clinically by pruritic lesions in typical locations; the crusted form is a rare manifestation. The diagnosis is usually established based on the clinical picture, but dermoscopy can be an important complementary method, as it allows the observation of a brownish triangular structure with a hang-glider appearance. A case of crusted scabies is reported; the magnification of the images obtained by digital dermoscopy allowed the demonstration of a structure usually observed only with videodermoscopy.